Measure and Analysis of the Bullwhip Effect in Supply Chain When Demand Correlation Exists between Two Market Groups Under the First-Order Moving-Average Demand Processes - Sirikasemsuk, Kittiwat; Sirikasemsuk, Sarawut (International Journal of Engineering and Technology, 2018)
With supply chains becoming increasingly global, the issue of bullwhip effect, a phenomenon attributable to demand fluctuation in the upstream section of the supply chains, has received greater attention from many researchers. The phenomenon in which the variation of upstream members' orders is amplified than the variation of downstream members' demands in the supply chain is called the bullwhip effect (BWEF). Most of existing research studies did not realize the demand dependency of market demands. Thus, this research focused on the study of the influence of the demand correlation coefficient between two market groups on the BWEF. The incoming demand processes are assumed the separate first-order moving-average, [MA(1)] demand patterns. The scope of the supply chain structure used in this research is composed of one manufacturer and two distribution centers. The general result reveals that the coefficient of correlation is one of several factors affecting the BWEF.Â